PERSEPSI MAHASISWA IAIN TULUNGAGUNG TERHADAP PELAKSANAAN PROGRAM MAGANG DI MTSN 2 KOTA BLITAR - Ahmad Fahrudin; Arbaul Fauziah (Ta'allum: Jurnal Pendidikan Islam, 2020)
Abstract: The aim of this study was to evaluate the perceptions of IAIN Tulungagung students on the implementation of the internship program at MTSN 2 Blitar. This study was conducted on March to November 2020. This study used a qualitative approach and secondary data was analyzed descriptively and exploratively. The informants in this study were students of the Tarbiyah and Teacher Training Faculty (FTIK) IAIN Tulungagung who carried out the Internship program 1 and 2 at MTsN 2 Blitar, East Java. Data were collected using questionnaires, observation, documentation, and interviews. As much as 92% of students stated that there was preparation or provision of apprenticeship program at IAIN Tulungagung before the students went to the field. At the same percentage, students claimed to be happy in carrying out an internship program. This was indicated by the existence of special preparations every day before entering the class which was stated by 84% of students. All students (100%) had high enthusiasm for teamwork. According to 84% of students, this was triggered by the atmosphere in the partner institutions to support the implementation of internships. Thus, all students (100%) can conduct socialization in a flexible manner with the school. Even though the implementation of internship was well, there were 30% of students who stated that there were obstacles in its implementation. The condition caused the dissatisfaction was felt by 23% of students. As many as 76% of students stated that there were administrative tasks and as many as 69% of students stated that there were several other tasks given by the school during the internship. Keywords: enthusiasm, internship, student, perception